Diffusion tensor imaging of neurocognitive profiles in a community cohort living in marginal housing. Issue 3 (6th February 2019) - Gicas, Kristina M.; Cheng, Alex; Rawtaer, Iris; Willi, Taylor S.; Panenka, William J.; Lang, Donna J.; Smith, Geoff N.; Vila‐Rodriguez, Fidel; Leonova, Olga; Giesbrecht, Chantelle J.; Jones, Andrea A.; Barr, Alasdair M.; et al.
Abstract: Objective: We investigated white matter differences associated with distinct neurocognitive profiles derived from a large cohort of marginally housed persons with comorbid physical and mental illnesses. Our prior work identified three profile cluster groups: a high functioning group (Cluster 1), a low functioning group with relative strength in decision‐making (Cluster 3), and an intermediary group with a relative decision‐making weakness (Cluster 2). This study extends previous findings of cortical gray matter differences between these groups with evidence for putative neurodevelopmental abnormalities in the low cognitive functioning group (i.e., Cluster 3). We hypothesized that altered white matter diffusion would be associated with the lowest functioning neurocognitive profile and would be associated with previously observed gray matter differences. Method: Participants from a socially impoverished neighborhood in Vancouver, Canada underwent neurocognitive evaluation and neuroimaging. We performed Tract‐Based Spatial Statistics using diffusion tensor imaging data from 184 participants to examine whole‐brain differences in white matter microstructure between cluster analytically derived neurocognitive profiles, as well as unitary neurocognitive measures. Correlations between frontal gray and white matter were also examined. Results: Cluster 3 showed increased diffusion in predominately bilateral frontal and interhemisphere tracts (vs. Clusters 1 and 2), with relatively greater diffusion in the left hemisphere (vs. Cluster 1). Differences in radial diffusivity were more prominent compared with axial diffusivity. A weak association between regional frontal fractional anisotropy and previously defined abnormalities in gyrification was observed. Conclusions: In a socially marginalized sample, we established several patterns in the covariation of white matter diffusion and neurocognitive functioning. These patterns elucidate the neurobiological substrates and vulnerabilities that are apt to underlie functional impairments inherent to this complex and heterogeneous population. Abstract : Three groups with distinct neurocognitive profiles have been identified in a cohort of marginally housed persons with comorbid physical and mental illnesses. The lowest functioning group exhibited bilateral frontal and interhemispheric alterations in white matter diffusion. Weak associations between white matter diffusion and cortical gray matter morphology were also observed.